Penerapan Model Creative Problem Solving untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas I Sekolah Dasar - Saputri, Rosiyani Dwi (Universitas Sebelas Maret, 2022)
The purpose of this research is to improve the learning outcomes of students in the Mathematics course in grade I elementary schools with the Creative Problem Solving (CPS) learning model. The research conducted was Classroom Action Research (PTK) in two cycles, with each cycle consisting of two meetings. The stages of each cycle are planning, implementing, observing and reflecting. In the initial conditions before carrying out the classical mastery action of students by 25%, the first cycle with classical completeness was 63.85%, and the second cycle with classical completeness was 82.5%. These results indicate that the Creative Problem Solving (CPS) learning model can improve student learning outcomes, especially the Class I Maths at SDN Tegalrejo, Pasarkliwon, Surakarta for the 2021/2022 Academic Year.